Correlation between Teachers’ Leisure Time Activities and their Teaching Styles - Blažević, Ines; Matijašević, Bruno (Acta Paedagogica Vilnensia, 2025)
The aim of this paper is to explore the ways teachers spend their free time in relation to their place of residence, differences in teaching styles based on career advancement, class type, and school type, and the interrelation between teachers’ free-time activities and their teaching styles. This topic was examined by using a two-part questionnaire containing the Leisure Time Activity Questionnaire (LTAQ) and the Staffordshire Evaluation of Teaching Styles questionnaire (SETS). A total of 1492 class and subject teachers voluntarily participated in the research. The results of the empirical part of the research indicate that teachers usually spend their leisure time in organized activities with friends and family, but statistically significant differences were found in teachers’ leisure time activities with regard to their place of residence (city/village/island). Furthermore, the results of teachers’ self-assessments show that they most often take on the role of a lecturer, but also a student-oriented teacher. Statistically significant differences have been identified depending on the type of class unit they teach (regular/combined), the type of school (central/branch) they work in, and qualification status they have achieved (mentor/advisor/excellent advisor). A mutual correlation in teachers’ ways of spending leisure time and their teaching styles has also been established.